Experiences of family caregivers in dealing with cases of advanced breast cancer: a qualitative study of the sociocultural context in Punjab, Pakistan - Sadia Jabeen; Rubeena Zakar; Muhammad Zakria Zakar; Florian Fischer (BMC Public Health, 2024)
Abstract Background Patients with advanced breast cancer require consistent help and support from family caregivers. These caregivers often endure financial burdens and psychological stress, with their experiences significantly influenced by sociocultural factors. This study aims to explore the experiences of family caregivers of advanced breast cancer patients in Punjab province, Pakistan. Methods Data was collected through in-depth interviews with fifteen family caregivers of advanced breast cancer patients in three major cities of Punjab, Pakistan. Caregivers, who had been in close contact with the patient for the last two years, were purposively sampled from five major hospitals. The data was analyzed using thematic analysis. Results The study revealed that the experiences of family caregivers are deeply rooted in the sociocultural context. Key themes identified include social responsibility and cultural reciprocity norms; limited awareness and mobility options for caregivers; financial responsibility and strain; impacts of beauty myths and shyness on caregiving attitudes and decisions; the stressful and emotional nature of caregiving; treatment perspectives influenced by social groups; challenges in consulting male physicians and associated stigma; the role of religious beliefs in caregiving; and stress management, with religion often being a coping mechanism. These factors can contribute to delayed treatment decisions for patients. Conclusions Family caregivers are crucial in facilitating timely treatment decisions for advanced breast cancer patients in the Pakistani context. To minimize treatment delays and alleviate caregiver stress, addressing sociocultural barriers in care-seeking is essential. A tailored approach, considering sociocultural and religious factors, is imperative for the management and early diagnosis of breast cancer, necessitating appropriate policymaking and implementation.